A Study of Complaints by Authorities and Public at East Coast Rail Link (ECRL) Project in Section 2 (Pasir Puteh) - Roaini, Ikmal; Muhamad Faiz Abd Latif ,; Muhamad Sulaiman Al Yaakubi Suhaimi , (Progress in Engineering Application and Technology, 2024)
The East Coast Rail Link (ECRL) project, managed by Malaysia Rail Link Sdn Bhd (MRLSB), aims to enhance Malaysia's transportation infrastructure and regional strategic objectives along its 665 km span from Kota Bharu to Port Klang. However, Section 2 of the project ECRL faces numerous public complaints and concerns have emerged due to nearest residential areas. This study investigates these issues by analyzing authorities and villagers’ complaints from January to December 2022 by focusing on public safety, dust/pollution, and flood/drainage. Through methodical classification and analysis, effective mitigation plans are developed to address these concerns by ensuring project success and community trust. The study emphasizes the importance of proactive measures to prevent further complications and highlights the necessity of comprehensive, regulatory-compliant strategies to optimize project outcomes and minimize negative impacts on affected communities. Through regular inspections, advanced techniques, and close coordination with authorities and villagers’, the study identifies strategies such as reinforcing slope protections, ensuring road diversions meet safety standards, controlling construction dust, and maintaining effective irrigation systems. The results highlight the importance of proactive maintenance and comprehensive strategies to prevent further complications and minimize negative impacts on affected communities. Proactive maintenance scheduling is crucial for maintaining infrastructure integrity and community well-being with demonstrating a commitment to continuous improvement. This approach enhances connectivity, stimulates economic growth, and improves the overall quality of life for affected communities. This study contributes to the community relations by addressing and mitigating complaints from authorities and the public regarding the East Coast Rail Link (ECRL) in Section 2 (Pasir Puteh).